2017
DOI: 10.1590/s1983-41952017000100005
|View full text |Cite
|
Sign up to set email alerts
|

Tools for assessing damage in concrete affected by AAR coming from fine and coarse aggregates

Abstract: Tools for assessing damage in concrete affected by AAR coming from fine and coarse aggregatesTécnicas para a avaliação da deterioração proveniente da reação álcali-agregado (RAA) gerada pela presença de agregados reativos graúdos e miúdos Abstract ResumoOver the last few years, comprehensive management programs for the diagnosis and prognosis of alkali-aggregate reaction (AAR) in aging concrete structures were developed in North America, based on a series of laboratory test procedures. Although promising, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The first ASR damaged structure reported was the Parker Dam in Arizona in 1941 [33]. Later, various structures were diagnosed to be affected by ASR, including for instance the turbine foundation of the Ikata power plant in Japan [34], Bibb Graves Bridge in Albama, USA [35], Seabrook Nuclear Power Plant in New Hampshire, USA [36], Vosnasvej Bridge in Denmark [37], Robert-Bourassa/Charest overpass in Quebec, Canada [38], and the Warsak Dam in Pakistan [39,40]. The deleterious effects of ASR in concrete structures can be minimized by controlling the alkali content, minimizing reactive silica, reducing the exposure to water, and addition of alkali-silica expansion inhibitor admixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The first ASR damaged structure reported was the Parker Dam in Arizona in 1941 [33]. Later, various structures were diagnosed to be affected by ASR, including for instance the turbine foundation of the Ikata power plant in Japan [34], Bibb Graves Bridge in Albama, USA [35], Seabrook Nuclear Power Plant in New Hampshire, USA [36], Vosnasvej Bridge in Denmark [37], Robert-Bourassa/Charest overpass in Quebec, Canada [38], and the Warsak Dam in Pakistan [39,40]. The deleterious effects of ASR in concrete structures can be minimized by controlling the alkali content, minimizing reactive silica, reducing the exposure to water, and addition of alkali-silica expansion inhibitor admixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The reductions established in the study by Sanchez et al [3], described in Table 3, were applied in order to study the distribution of cracking in the cracking fields along these reductions. Although the analysis of the reductions in the mechanical properties as a result of the expansion due to the AAR is complicated, and there are many contradictory results in the literature, the choice of parameters studied by Sanchez et al [3] was due, from among the authors that related the degradation of concrete mechanical properties to the expansion due to the AAR, described herein, and is experimental study that provided the most complete parameters on the subject.…”
Section: Resultsmentioning
confidence: 99%
“…The literature includes several experimental studies on the alkali-aggregate reaction, namely Gomes [1], for example, who studied experiments on the structural recovery of foundation caps; Sanchez et al [2] addressed a new method called the accelerated Brazilian concrete prism test (ABCPT), in which the results indicated that that test had great potential to detect aggregate reactivity in current engineering projects; Sanchez et al [3], who presented test results from the Stiffness Damage Test (SDT) and the microscopic evaluation of the Damage Rating Index (DRI) to assess the level of damage to the AAR-affected concrete. However, there are only a few numerical studies on expressions of such reactions on foundation caps.…”
Section: Introductionmentioning
confidence: 99%
“…Expedited testing for ASR and relevant standards are developed for early detection of ASR [21][22][23][24]. ASR Laboratory evaluation measures has average reliability due to the difference between lab conditions and the environmental conditions a concrete member is subjected to during its service life [25][26][27][28][29]. Other ASR detection methods includes the development of field exposure site to predict ASR through full scale expansion testing of hardened concrete members [30,31].…”
Section: Literature Reviewmentioning
confidence: 99%